2010
DOI: 10.1186/1742-4690-7-102
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell subsets dynamics and cytokine production in SIVmac239-infected Chinese rhesus macaques

Abstract: BackgroundSeveral studies have demonstrated that SIV infection progresses more slowly to experimental AIDS in Chinese rhesus macaques (Ch Rhs) than in Indian rhesus macaques (Ind Rhs). Here we investigated the dynamic and functional changes in dendritic cell (DC) subsets in SIVmac239-infected Ch Rhs.ResultsThe numbers of both mDC and pDC strongly fluctuated but were not significantly changed during the acute and chronic phases of infection. However, the concentration of both poly (I:C)-induced IL-12 and HSV-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…The SIVmac239-infected Chinese rhesus macaques were treated as previously described. 13 The SIVmac239-infected macaques were housed at the animal biosafety level-3 laboratory. The three macaques (00067, 00079 and 01035) that were found to have CD4 1 T-cell counts below 500 events per microliter were considered to be in the late infection stage while the others were considered to be chronically infected.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SIVmac239-infected Chinese rhesus macaques were treated as previously described. 13 The SIVmac239-infected macaques were housed at the animal biosafety level-3 laboratory. The three macaques (00067, 00079 and 01035) that were found to have CD4 1 T-cell counts below 500 events per microliter were considered to be in the late infection stage while the others were considered to be chronically infected.…”
Section: Animalsmentioning
confidence: 99%
“…In the virion stimulation tests, the SIVmac239 virions were used at a p27 concentration of 200 ng/ml, while the herpes simplex virus (HSV) virions were used as previously described. 13 A chloroquine diphosphate salt (Sigma, Oakville, Ontario, Canada) solution was used in pDC activation tests at a concentration of 100 mM for 24 h and in T-cell activation tests at a concentration of 5 mM as described by Martinson et al 9 …”
Section: Peripheral Blood Mononuclear Cell (Pbmc) Isolation and Stimumentioning
confidence: 99%
See 1 more Smart Citation
“…The viral load in plasma was measured by quantitative PCR for SIV gag RNA as described by Xia et al [45]. The probe and primers are listed in Supplementary Table S1.…”
Section: Quantitative Pcr For Plasma Viral Load and Proviral Loadmentioning
confidence: 99%
“…Their absolute numbers were calculated from the absolute numbers of CD4 ? T cells (data shared, [29]). Although the number of Treg cells in different monkeys varied after challenge, a one-sample t-test analysis showed that the Treg cells increased significantly in the first month and remained at a high level (more than 11.06%) thereafter during the entire course of the study (p\0.01) ( Fig.…”
Section: Increase In Treg Cell Counts After Sivmac239 Infectionmentioning
confidence: 99%